Comparative study of two reprocessing methods for formalin fixed paraffin embedded tissue. (3rd July 2022) - Lunetta, Matthew; Grivois, Megan; Hansen, Christopher; Seery, Peter; Felty, Cameron; Rizzo, Elizabeth; Jackson, Christopher
ABSTRACT: Formalin fixed paraffin embedded tissue occasionally requires reprocessing if the histologic quality of a section is inadequate for clinical diagnosis. The Pat Dry (PD) and the Serial Xylene (SX) methods are two techniques described in the literature to reprocess under-fixed and/or under-processed tissue samples. To date, no study has compared the effects of these methods on the histologic quality of tissue sections, cost, and turnaround times. In the present study, these two methods were evaluated on 129 tissue samples taken from 40 submitted clinical specimens, 3 blocks per sampled location. Before processing, sample Group 1 (Control) was cut at routine 3–5 mm thickness. Sample Groups 2 and 3 were cut at 10 mm to ensure the thicker tissues would be poorly processed. Histotechnicians performed a subjective evaluation of all the samples at the time of embedding and microtomy. Hematoxylin and eosin stained sections from all samples were scored for histologic quality by two pathology residents. Thicker samples (Groups 2 and 3) were then reprocessed using either PD or SX methods, re-sectioned, stained, and then re-scored by the pathology residents. The two reprocessing methods equally improved quality scores and reduced the fraction of slides that were rejected. The PD method average preparation time was 66 minutes as compared to 250 minutes for the SX method. The PD method was easier to perform than the SX method, required less reagent, and was less susceptible to reagent spillage than the SX method.